2020
DOI: 10.13189/ujph.2020.080402
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices towards Hypertension among Hypertensive Patients in Rural Area, Tanvè (Benin)

Abstract: Hypertension mortality could be reduced by compliance with treatments and hygienic rules. The study aimed to assess the knowledge, attitudes and practices (KAPs) towards hypertension among hypertensive patients at Tanvè (Benin) in 2018. Materials and Methods: This was a cross-sectional study. It included, people aged 25 and over, followed in Tanvè Health Study and screened hypertensive during the 2017 visit. An individual interview was used for the data collection in 2018. The evaluation of the KAPs was made b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Similarly, few global KAP studies on chronic diseases identified poor patient knowledge and inadequate practices for secondary prevention. Therefore, providing correct information and support for adopting good behaviours in the target population suffering from these diseases is critical [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, few global KAP studies on chronic diseases identified poor patient knowledge and inadequate practices for secondary prevention. Therefore, providing correct information and support for adopting good behaviours in the target population suffering from these diseases is critical [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, VANITHA et al found no daily consumers of even one serving of fruit among hypertensive patients where only 3% took three servings of vegetables daily [21]. The impact of a substantial consumption of vegetables and fruits on BP reduction was already demonstrated in hypertensive patients [25]. The same is true for garlic [26].…”
Section: Evaluation Of Patient Dietary Habits and Relationship With B...mentioning
confidence: 99%